Diorganotin(IV) alkylcyclohexyldithiocarbamate compounds: synthesis, characterization and biological activities (Sebatian diorganostanum(IV) alkilsikloheksilditiokarbamat: sintesis,pencirian dan aktiviti biologi) - Normah Awang,; Ibrahim Baba, (Universiti Kebangsaan Malaysia, 2012)
Three new compounds of dibutyltin(IV) with N alkylcyclohexyldithiocarbamate were successfully synthesized using in situ methods. Elemental analysis data of these complexes were in agreement with the general formula of (C4H9)2Sn[S2CNR(C6H11)]2 (R = CH3, C2H5, i-C3H7). Infrared spectra showed that the thioureide bands, ν(C=N) appeared in the region of 1475 - 1479 cm-1, ν(C=S) bands in the region of 978 - 998 cm-1 and ν(Sn-S) bands in the region of 375 – 389 cm-1. Crystal structure of dibutyltin(IV) ethylcyclohexyldithiocarbamate showed a triclinic system and space group P-1. The crystal structure of the dithiocarbamate ligands were bidentically chelated to the tin atom with Sn-S unsymmetrical: Sn(1)-S(1) = 2.9255(11) and Sn(1)-S(2) = 2.5419(10); Sn(1)-S(3) = 2.8922(9) and Sn(1)-S(4) = 2.5293(10)Å. These compounds were screened for antibacterial activity against four bacteria species using the disc diffusion method. The results showed that (C4H9)2Sn[S2CN(i-C3H7)(C6H11)]2 was mildly active against those three bacteria. Whereas all of these compounds exhibited in vitro cytotoxicity activity toward human leukemic promyelocites HL-60 cell line with CD50 values lower than 1.00 μg/mL.